Gagasan Komunikasi Islam dalam Karya Sarjana Komunikasi di Indonesia - Holy Rafika Dhona; Risky Wahyudi (Jurnal Komunikasi Islam, 2022)
This article aims to examine how academics in the field of communication comprehend Islamic communication as represented within scientific publications, especially scientific journals. This study reports on how academics discuss Islamic communication within 227 articles published in Indonesian journals indexed by Garba Reference Digital (Garuda) for the 2016-2020 period. Using descriptive quantitative content analysis, this study states that most Islamic communication writings tend to position Islam as "an object", rather than as "a perspective". In this regard, Islamic communication is often put into the normative realm, regarding manners and rules of conduct when doing communication.